Kepemimpinan Kiai di Pondok Pesantren â€œStudi Analisis Perilaku Kiai Non-Warisan dalam Organizational Developmentâ€ - Wahidah, Finadatul (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2018)
The most varied Islamic educational institution is boarding school. In the leadership of a boarding school, a kiai is the most important element. Kiai pioneers, nurtures, determines the mechanism of learning; and curriculum and colors the boarding school in everyday life according to the skills and trends he has. Zamakhsyari Dhofier states that the kiai is a title given by the community to an Islamic scholar who owns or who is the leader of the boarding school and teaches the classical Islamic books to the santri. In addition, the title of kyai is also called the pious person (the person who is expert in his Islamic knowledge). In the midst of today's modernization civilization, the term kiai has undergone a transformation of meaning. These are the term inherited kiai and non-inherited kiai. The kiai title is given to someone who does not have expertise in religious knowledge, but has a high spirit to establish an Islamic boarding school and dedicate his life in the way of Allah SWT. Furthermore, he who disseminates the teachings of Islam through educational activities can be called as non-inherited kiai . This research was conducted in a boarding school in Jember namely Al-Barokah An-Nur Jember. Founder of Al-Barokah boarding school An-Nur is someone who does not have expertise in Islamic science, but has a high ghirah in establishing boarding school. We may call this kind of Kiai by non-inherited kiai. The focus of this study are: (1) how are characteristics of Al-Barokah An-Nur boarding school; (2) how are organization management and development (organizational development) in Al-Barokah AN-Nur boarding school; (3) how is the kiai leadership behavior in managing Al-Barokah AN-Nur; The purpose of this study is to reveal and analyze the leadership of kiai (inherited kiai and non-inherited kiai) in developing the boarding school he founded. This research was conducted using qualitative research type and case study approach. The data collection techniques use interview, observation, and documentation. Data analysis uses interactive model Miles Huberman. Keywords: Islamic boarding school, Kiai, Organizational Development